Evaluation of autoantibodies as predictors of treatment response and immune‐related adverse events during the treatment with immune checkpoint inhibitors: A prospective longitudinal pan‐cancer study. (16th March 2022) - Barth, Dominik A.; Stanzer, Stefanie; Spiegelberg, Jasmin; Bauernhofer, Thomas; Absenger, Gudrun; Posch, Florian; Lipp, Rainer; Halm, Michael; Szkandera, Joanna; Balic, Marija; Gerger, Armin; Smolle, Maria A.; et al.
Abstract: Background: The presence of autoantibodies in the serum of cancer patients has been associated with immune‐checkpoint inhibitor (ICI) therapy response and immune‐related adverse events (irAEs). A prospective evaluation of different autoantibodies in different cancer entities is missing. Materials and Methods: In this prospective cohort study, we included a pan‐cancer cohort of patients undergoing ICI treatment and measured a comprehensive panel of autoantibodies at treatment start and at the time point of first response evaluation. The presence and induction of autoantibodies (ANA, ENA, myositis, hepatopathy, rheumatoid arthritis) in different cancer entities were assessed and the association between autoantibodies and disease control rate (DCR), objective response rate (ORR), and progression‐free survival (PFS), as well as the development of grade 3 or higher irAEs were evaluated by logistic regression models, cox proportional hazard models, and Kaplan–Meier estimators. Results: Of 44 patients with various cancer entities, neither the presence of any positive autoantibody measurement nor the presence of positive antinuclear antibodies (ANA) [≥1:80] at baseline was associated with the examined clinical endpoints (DCR, ORR, PFS) in univariable and multivariable analyses. After 8–12 weeks of ICI treatment, DCR, ORR, and PFS did not significantly differ between patients with and without any positive autoantibody measurement or positive ANA titers. The frequency of irAEs did not differ depending on autoantibody status of the patients. Conclusion: Autoantibodies at treatment initiation or induction after 8–12 weeks of ICI treatment are not associated with treatment efficacy as indicated by DCR, ORR, and PFS or higher grade irAEs. Abstract : Autoantibodies at treatment initiation or induction after 8‐12 weeks of ICI treatment are not as‐sociated with treatment efficacy as indicated by DCR, ORR and PFS or higher grade irAEs in a prospective longitudinal study.